Free water imaging in healthy brain aging and first signs of brain pathology. (20th December 2022) - Berger, Martin; Pirpamer, Lukas; Hofer, Edith; Ropele, Stefan; Pasternak, Ofer; Enzinger, Christian; Schmidt, Reinhold; Koini, Marisa
Abstract: Background: Brain aging is associated with cerebral small vessel disease (SVD). Recently, it was suggested that SVD is mainly driven by increases of extracellular free water (FW). The aim of the present study was to examine the association of FW, conventional and FW‐corrected diffusion tensor imaging (DTI) parameters (fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), axial diffusivity (AD)) with aging. The second aim was to determine if differences in FW and DTI parameters exist between individuals with first signs of pathology and healthy elderly controls regarding metrics that are not associated with age. Method: We examined 87 healthy elderly (age: M = 66.34, SD = 9.82) and 87 individuals with first signs of cerebral pathology (age: M = 68.14, SD = 9.18) of the Austrian Stroke Prevention Family Study. Individuals with first signs of cerebral pathology were defined as having WMH score >1, presence of lacunes and/or microbleeds. FW in global normal appearing white matter (NAWM) as well as conventional and FW‐corrected DTI parameters were used in correlation analyses to assess their association with age. ANOVA adjusted for multiple comparison was used to determine the differences in FW and FW‐corrected DTI metrics between individuals with initial signs of SVD and healthy controls. Result: FW in NAWM as well as non‐FW‐corrected DTI were significantly associated with age in the total sample and both stratified groups (range of |r|: 0.24‐0.49). No correlation between FW‐corrected DTI measures and age were found. Differences between individuals with and without first signs of pathology were only identified for FW in NAWM. Conclusion: The association between uncorrected conventional DTI parameters and age is mainly driven by the amount of FW, calling for caution when interpreting uncorrected DTI scores. In contrast, FW appears to be a sensitive marker at very early, clinically silent, signs of SVD.